ANALYZING THE EFFECT ISO 14001 ON FIRM PERFORMANCE: EMPIRICAL EVIDENCE BEFORE AND DURING THE COVID-19 PANDEMIC - Hidayah, Ismi Nur; Irwan Trinugroho (MANAJEMEN DEWANTARA, 2024)
Research on environmental performance and firm performance is a topic that has been widely studied but has not been carried out in many developing countries. In addition, the research period was carried out with a focus on the pre-pandemic and the COVID-19 pandemic. For this reason, the main objective of this paper is to analyze the impact of ISO 14001 on company performance from the perspectives of financial performance and environmental performance of companies in Indonesia before the pandemic and during the COVID-19 pandemic. We obtained data for a sample of 66 companies divided into six types of industrial sectors, with a research period from 2018 to 2021. We use panel data regression with the random effect model for this research. The results obtained show that the application of the ISO 14001 certificate has an effect on the firm’s environmental performance but has no effect on the firm’s financial performance.